Demethyleneberberine Alleviates Pulmonary Fibrosis through Disruption of USP11 Deubiquitinating GREM1 - Chuang Ge; Mengsheng Huang; Yanhong Han; Chang Shou; Dongyin Li; Yubin Zhang (Pharmaceuticals, 2024)
Background: Idiopathic pulmonary fibrosis (IPF) is a fatal and chronic interstitial lung disease. Intricate pathogenesis of pulmonary fibrosis and only two approved medications with side effects and high cost bring us the challenge of fully understanding this lethal disease and urgency to find more safe and low-cost therapeutic alternatives. Purpose: Demethyleneberberine (DMB) has been demonstrated to have various anti-inflammatory, antioxidant, antifibrosis and anti-cancer bioactivities. The objective of this study was to evaluate the effect of DMB on pulmonary fibrosis and investigate the mechanism. Methods: Bleomycin (BLM)-induced pulmonary fibrosis was established in mice to evaluate the antifibrotic effect of DMB in vivo. A549 and MRC5 cells were used to evaluate the effect of DMB on epithelial–mesenchymal transition (EMT) and fibroblast–myofibroblast transition (FMT) in vitro. High throughput sequencing, biotin–avidin system and site-directed mutagenesis were applied to explore the mechanism of DMB in alleviating pulmonary fibrosis. Results: DMB alleviated BLM-induced pulmonary fibrosis in vivo by improving the survival state of mice, significantly reducing pulmonary collagen deposition and oxidative stress and improving lung tissue morphology. Meanwhile, DMB was demonstrated to inhibit epithelial–mesenchymal transition (EMT) and fibroblast–myofibroblast transition (FMT) in vitro. High throughput sequencing analysis indicated that GREM1, a highly upregulated profibrotic mediator in IPF and BLM-induced pulmonary fibrosis, was significantly downregulated by DMB. Furthermore, USP11 was revealed to be involved in the deubiquitination of GREM1 in this study and DMB promoted the ubiquitination and degradation of GREM1 by inhibiting USP11. Remarkably, DMB was demonstrated to selectively bind to the Met776 residue of USP11, leading to disruption of USP11 deubiquitinating GREM1. In addition, DMB presented an equivalent antifibrotic effect at a lower dose compared with pirfenidone and showed no obvious toxicity or side effects. Conclusions: This study revealed that USP11/GREM1 could be a potential target for IPF management and identified that DMB could promote GREM1 degradation by inhibiting USP11, thereby alleviating pulmonary fibrosis.